Ecology of millipedes (Diplopoda) in the context of global change Jean-François - Jean-François David (Soil Organisms, 2009)
Current knowledge on the effects of climate, food quality and land cover on millipedes is reviewed, to explore the potential responses of this arthropod group to global change. Climate warming could result in higher rates of population growth and have a positive effect on the abundance of some temperate species. The generality of this finding is evaluated in relation to the life history and current distribution of species. At low latitudes, interactions with more severe droughts are likely and could affect the composition of millipede communities. Elevated atmospheric CO2 and changes in plant community composition are expected to alter leaf litter quality, a major determinant of millipede fertility. This could significantly influence population growth rates, but the warming effect will be probably more important for decades. Land cover changes, mainly due to deforestation in the tropics and land abandonment in Europe, are critical to habitat specialists and could override any other effect of global change. At the landscape scale, habitat heterogeneity seems to be a good option for millipede conservation, even at the cost of some fragmentation.